Low-temperature synthesis and electrocatalytic application of large-area PtTe2thin films - Duesberg, Georg; Browne, Michelle; Shvets, Igor (My University, 2020)
The synthesis of transition metal dichalcogenides (TMDs) has been a primary focus for 2D nanomaterial research over the last 10 years, however, only a small fraction of this research has been concentrated on transition metal ditellurides. In particular, nanoscale platinum ditelluride (PtTe2) has rarely been investigated, despite its potential applications in catalysis, photonics and spintronics. Of the reports published, the majority examine mechanically-exfoliated flakes from chemical vapor transport (CVT) grown crystals. This method produces high quality-crystals, ideal for fundamental studies. However, it is very resource intensive and difficult to scale up meaning there are significant obstacles to implementation in large-scale applications. In this report, the synthesis of thin films of PtTe2 through the reaction of solid-phase precursor films is described. This offers a production method for large-area, thickness-controlled PtTe2, potentially suitable for a number of applications. These polycrystalline PtTe2 films were grown at temperatures as low as 450 °C, significantly below the typical temperatures used in the CVT synthesis methods. Adjusting the growth parameters allowed the surface coverage and morphology of the films to be controlled. Analysis with scanning electron- and scanning tunneling microscopy indicated grain sizes of above 1 µm could be achieved, comparing favorably with typical values of ~50 nm for polycrystalline films. To investigate their potential applicability, these films were examined as electrocatalysts for the hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR). The films showed promising catalytic behavior, however, the PtTe2 was found to undergo chemical transformation to a substoichiometric chalcogenide compound under ORR conditions. This study shows while PtTe2 is stable and highly useful for in HER, this property does not apply to ORR, which undergoes a fundamentally different mechanism. This study broadens our knowledge on the electrocatalysis of TMDs.
PUBLISHED
cited By 5
Keywords: transition metal dichalcogenides (TMDs); 2D nanomaterial; nanoscale; transition metal dichalcogenides (TMDs); 2D nanomaterial; nanoscale